1980
DOI: 10.1055/s-2007-999233
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Production of VLDL-Triglycerides. Dependence of Portal Substrate and Insulin Concentration

Abstract: Insulin has an exacerbating effect on endogenous hypertriglyceridemia. Experiments were carried out in order to study the acute effects of insulin in 6 patients with endogenous hypertriglyceridemia and 6 controls. 0.1 Unit insulin/kg body weight was injected into the portal vein. Blood samples were taken from the portal and hepatic veins and analysed for FFA, glycerol, VLDL-triglycerides (VLDL-TG) and insulin. Liver blood flow was measured with cardiogreen. This technique allowed a study of the acute effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…This variability in response is understandable when the individual pathways are considered, because the total secretion rate after 24 h of carbohydrate hyperalimentation/hyperinsulinemia was a function of two opposing trends (Tables IV and V). The decreased secretion of preformed FA, coupled with an increase in de novo synthesis, could explain the conflicting results obtained in previous studies in which acute hyperinsulinemia either decreased (12,15,(50)(51)(52)(53) or did not affect (11, 54) VLDL secretion. Depending on the experimental factors, such as the selection of subjects, whether or not they were fasted, and in particular the duration and extent of hyperinsulinemia, the effect on one pathway may predominate.…”
Section: Discussionmentioning
confidence: 82%
“…This variability in response is understandable when the individual pathways are considered, because the total secretion rate after 24 h of carbohydrate hyperalimentation/hyperinsulinemia was a function of two opposing trends (Tables IV and V). The decreased secretion of preformed FA, coupled with an increase in de novo synthesis, could explain the conflicting results obtained in previous studies in which acute hyperinsulinemia either decreased (12,15,(50)(51)(52)(53) or did not affect (11, 54) VLDL secretion. Depending on the experimental factors, such as the selection of subjects, whether or not they were fasted, and in particular the duration and extent of hyperinsulinemia, the effect on one pathway may predominate.…”
Section: Discussionmentioning
confidence: 82%
“…Thus studies in humans have shown that intraportal infusion of insulin in humans results in a decrease in the secretion of VLDL-TAG [97]. Similarly, when humans are treated with insulin, the secretion of apoB "!!…”
Section: Acute Changes In Glycerolipid Partitioning During the Prandimentioning
confidence: 99%
“…Because both LDL cholesterol (3) and apo B 100 (4) levels are associated with atherosclerotic disease, an understanding of the control of hepatic apo B synthesis and secretion is important. Acute studies in man (5,6) suggest that insulin administration decreases hepatic secretion of VLDL. Using primary cultures of rat hepatocytes (7-1 1) and HepG2 cells (12,13), we (7,8) and others (9)(10)(11)(12)(13) have shown that insulin exposure for < 24 h inhibits the secretion of VLDL (8)(9)(10)(11)(12) and apo B (7,8,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%